English As An International Language: An Overview - Dewi, Anita (Journal of English and Education (JEE), 2012)
As indicated in the title, this paper provides a brief overview of English as an International Language (EIL) by elaborating it as a paradigm and discussing concepts that are closely related to it. In doing so, the paper covers sections of English in relation to globalisation, linguistic imperialism, other languages, identity, its varieties, language ecology, and its impacts. Prominent theories and previous research results are presented throughout the paper. In general, EIL as a paradigm suggests that the spread of English is no longer a simple result of migration or colonisation rather it involves multiple reasons, backgrounds, and issues. In the context of communication, EIL requires appropriateness and negotiation in the use and function of English among other languages, which would ideally lead to a “contemporary global linguistic ecology” (Phillipson and Skutnabb-Kangas, p. 20).